Accelerating breast MRI acquisition with generative AI models - Okolie, Augustine; Dirrichs, Timm; Huck, Luisa; Nebelung, Sven; Tayebi Arasteh, Soroosh; Nolte, Teresa; Han, Tianyu; Kuhl, Christiane K.; Truhn, Daniel (European Radiology, 2024)
Objectives To investigate the use of the score-based diffusion model to accelerate breast MRI reconstruction. Materials and methods We trained a score-based model on 9549 MRI examinations of the female breast and employed it to reconstruct undersampled MRI images with undersampling factors of 2, 5, and 20. Images were evaluated by two experienced radiologists who rated the images based on their overall quality and diagnostic value on an independent test set of 100 additional MRI examinations. Results The score-based model produces MRI images of high quality and diagnostic value. Both T1- and T2-weighted MRI images could be reconstructed to a high degree of accuracy. Two radiologists rated the images as almost indistinguishable from the original images (rating 4 or 5 on a scale of 5) in 100% (radiologist 1) and 99% (radiologist 2) of cases when the acceleration factor was 2. This fraction dropped to 88% and 70% for an acceleration factor of 5 and to 5% and 21% with an extreme acceleration factor of 20. Conclusion Score-based models can reconstruct MRI images at high fidelity, even at comparatively high acceleration factors, but further work on a larger scale of images is needed to ensure that diagnostic quality holds